Growth and production of nasturtium flowers in three hydroponic solutions - Melo,Evanisa Fátima RQ (2011)
This experiment was carried out during April to August 2003 in a greenhouse at the Universidade Federal de Santa Maria, Rio Grande do Sul state, Brazil. The growth and production of nasturtium flowers (Tropaeolum majus) in hydroponics NFT system was typified. Treatments were displayed in a 3x11 factorial, with six replications, in entirely randomized experimental design, and were composed of three nutrition solutions and 11 assessment dates. Each plant was separated between aerial part and root for the evaluation of dry mass. The blossoming started 49 days after the transplant (DAT). The plants presented good development in hydroponics, as well as growing dry mass, stature, leaf area and IAF, during the cycle. The culture's growth rate presented larger accumulation of leaf mass from 49 DAT on, in linear relation. Biological productivity was adjusted to a 2nd degree equation. Nutrition solutions did not show statistical differences, however, Furlani (1997) solution was the most reasonably priced.